Methods of registering and estimating the population of Ireland before 1864 - Wood, Herbert (Statistical and Social Inquiry Society of Ireland, 1912)
It was suggested to me that a paper on the means of proof of age available in this country would prove of interest to the members of this Society, and I have taken the opportunity of giving a slight sketch of such methods of ascertaining the population of Ireland, and its increase or decrease, as existed before 1864, or in other words, to examine in what way the functions of the Registrar General were performed before that year.
Read, 18th December, 1908.
Keywords: Demographic change, Ireland; Population count, Ireland, Methodology; Population count, Ireland, Statistical methods; 314.15